Comparative study of bone mineral density, phenotypes of emphysema in patients with or without established diagnosis of chronic airway disease - Reddy, M Chandra Sekhar; Sushmita, G Laxmi (Journal of Applied Pharmaceutical Research, 2024)
Background: Bone thinning and emphysema are established diseases caused by tobacco-related products proven beyond doubt. A paucity of literature available to establish the association between them. Objectives: To explore the association between the different emphysema subtypes and the presence of low bone mineral density among a population of active or former smokers with and without an established diagnosis of chronic obstructive pulmonary disease (COPD). Methods: 100 active and former smokers with chronic airway disease attending the Pulmonology Outpatient Department were identified, and they were administered clinical questionnaires, pulmonary function tests, chest computed tomography, and DEXA scans. Appropriate statistical tests were performed to analyze the association between the different emphysema subtypes, low bone mineral density, and smoking in the study participants. Results: Out of 100 samples, 80 % of the patients had low BMD (25 had osteoporosis, and 55 had osteopenia). Emphysema was more frequent and severe in patients with osteoporosis (63.2 vs. 36.8%, p=<0.01). For analyzing significant co-factors, a multivariable analysis was done, which yielded Body Mass Index (Odds ratio of 0.89 with a 95% Confidence Interval of 0.67–1.23) and the presence of centrilobular emphysema as most commonly associated with osteoporosis. (Odds ratio of 35.25, with a 95% confidence interval of 3.23 to 401.63). Conclusion: Patients having increased Body Mass Index (BMI) and the presence of centrilobular emphysema are having osteoporosis irrespective of their smoking status, which implicates BMI, and centrilobular emphysema has to be considered while evaluating COPD patients.